HROP68: A rare case of medullary pancreatic cancer—characterization and chemosensitivity of the first patient-derived cell line - von den Driesch, Jens; Flöttmann, Jana; Prall, Friedrich; Mullins, Christina S.; Linnebacher, Michael; Bürtin, Florian (Frontiers in Oncology, 2023)
Introduction Medullary Pancreatic Carcinoma (MPC) is a rare subtype of pancreatic ductal adenocarcinoma (PDAC). MPCs represent less than 1% of all pancreatic cancers and with only 26 cases in the literature, knowledge regarding drug response and treatment outcome is very limited. Material and Methods We present the case of a 64-year-old male patient with an MPC who was treated by left pancreatic resection and adjuvant chemotherapy. Due to local recurrence, the patient underwent intended curative reoperation. From both surgical specimens, patient-derived xenografts (PDX) and from the recurrence, also a patient-derived cell line (PDCL), were established. We subsequently performed an in-depth characterization of this cell line including phenotypic characterization, surface protein expression, growth and migratory performance as well as mutational analysis using whole-exome sequencing (WES). Additionally, in vitro drug sensitivity towards standard of care chemotherapeutic regimen and selected targeted therapies was evaluated. Results The pathological and molecular properties of this rare MPC case observed in the patient’s tumors are preserved in the corresponding PDX and the PDCL of HROP68Tu2. Despite displaying an “immunogenic phenotype” with marked T-cell infiltration and high-level expression of HLA II and PD-L1, molecular analysis revealed microsatellite stability but a multitude of mutations affecting KRAS, TP53, KAT6B, FOXG1, RUNX1 and GRIK2 among others. Furthermore, HROP68Tu2 cells were susceptible towards 5-FU, irinotecan, oxaliplatin, gemcitabine, paclitaxel and erlotinib as single-agents, but only a moderate synergistic response was seen to the drugs of the FOLFIRINOX regimen. Even worse, the drugs of the two combinations gemcitabine plus paclitaxel and gemcitabine plus erlotinib showed antagonistic effects. Moreover, lapatinib, PRIMA-Met1 and olaparib selected as targeted therapeutics according to the mutational profiles and protein expression also inhibited HROP68Tu2 cells’ growth. Conclusion This study illustrates the establishment of the first preclinical MPC models as well as the first in-depth characterization of a MCP PDCL. Since scientific and clinical knowledge of this rare pancreatic cancer type is very limited, the presented models contribute to a better understanding of MPC and might be a valuable tool for the development of future treatment options.